1999
DOI: 10.2109/jcersj.107.879
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Ion Polarizability, Optical Basicity and Metal (or Nonmetal) Binding Energy of Simple Oxides.

Abstract: A suitable relationship between free-ion polarizability and metal (or nonmetal) outermost binding energy has been searched on the basis of the similarity in physical nature between electron binding energy and ionization energy. It has been suggested that outermost core-level binding energy can be used for relative measuring the cation polarizability. In general, cation polarizability increases with decreasing metal (or nonmetal) binding energy. Highly polarizable cations possess low outermost binding energy. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 4 publications
1
31
0
Order By: Relevance
“…That is, in general, cation polarizability increases with decreasing metal (nonmetal) binding energy. They also found that a decreasing of metal binding energy in XPS spectra of simple oxides is accompanied with decreasing of O1s binding energy, that is related to increased optical basicity [29]. A relation between metal binding energy and O1s binding energy has been established in Sb 2 O 3 -B 2 O 3 and Bi 2 O 3 -B 2 O 3 glasses [27,30].…”
Section: Xps Spectra For the Glassesmentioning
confidence: 88%
See 1 more Smart Citation
“…That is, in general, cation polarizability increases with decreasing metal (nonmetal) binding energy. They also found that a decreasing of metal binding energy in XPS spectra of simple oxides is accompanied with decreasing of O1s binding energy, that is related to increased optical basicity [29]. A relation between metal binding energy and O1s binding energy has been established in Sb 2 O 3 -B 2 O 3 and Bi 2 O 3 -B 2 O 3 glasses [27,30].…”
Section: Xps Spectra For the Glassesmentioning
confidence: 88%
“…5-8 for xZnO10Bi 2 O 3 -(90 À x)B 2 O 3 glasses, therefore, indicate that all binding energies corresponding to the B1s, Zn2p 3/2 , Bi4f, and O1s core level tend to decrease with increasing ZnO or the substitution of ZnO for B 2 O 3 . Dimitrov and Komatsu [29] suggested that outermost corelevel binding energy in simple oxides can be used for relative measuring the cation polarizability. That is, in general, cation polarizability increases with decreasing metal (nonmetal) binding energy.…”
Section: Xps Spectra For the Glassesmentioning
confidence: 99%
“…According to Ref. (9), a systematic periodic change of the polarizability against the binding energy has been observed in the isoelectronic series. It has been suggested that outermost core-level binding energy can be used for relative measure of the cation polarizability.…”
Section: Cation Polarizability and Metal Or (Nonmetal) Binding Energymentioning
confidence: 92%
“…Recently, on the basis of the similarity in the physical nature of the ionization energy (IE) and binding energy (BE), Dimitrov and Komatsu (9) have found that in the case of a large number of simple oxides generally cation polarizability increases with decreasing metal (or nonmetal) binding energy. The term metal (or nonmetal) binding energy (E ) was introduced to denote both binding energy of the outermost orbital of a cation in an oxide (E ) as well as the binding energy of the same orbital in the corresponding pure element (E ).…”
Section: Cation Polarizability and Metal Or (Nonmetal) Binding Energymentioning
confidence: 99%
See 1 more Smart Citation